OP0338 Frequency of comorbidities in jia patients – results of an observational cohort study. (15th June 2017) - Minden, K; Betenstehl, N; Klotsche, J; Seipelt, E; Tatsis, S; Foeldvari, I; Ganser, G; Horneff, G
Abstract : Background: Juvenile idiopathic arthritis (JIA) is a chronic inflammatory disease that often persists into adulthood. In addition to disability and poorer quality of life, JIA is associated with increased long-term morbidity and mortality. The long-term risk of comorbidities in JIA patients is uncertain and guidance on risk assessment is not currently available. Objectives: To determine the frequency of comorbid conditions in adult JIA patients. Methods: Patients with JIA transferred from the biologic registry BIKER to the follow-up (FU) registry JuMBO were included in this analysis. All comorbidities, except for serious infections, prospectively recorded by physicians to BiKeR or JuMBO were considered. Comorbidity rates among the various JIA categories were assessed. The Medical Dictionary for Regulatory Activities (MedDRA) was used for disorder coding. Differences in the occurence of comorbidities between JIA categories were analyzed by multinomial logistic regression. Results: A total of 1, 022 young adults (67% female) with JIA and a mean FU of 7.8 (SD=3.5) years (ys) were included in this analysis. The patients' mean age was 22.5 ys (SD=3.7), and disease duration was 12.9 ys (SD=5.9) at the last FU. The majority were classified as polyarticular JIA (36.4%) at BiKeR enrollment. Patients had received a mean of 2.9 (SD=1.3) DMARDs, 77% were ever treated with biologics. Comorbidities were reported for more than half of the patients (54%), 24.5% of the conditions were stated for the first time in adult age. Eye disorders were the most common comorbid condition group (15.1%), followed by skin and subcutaneous tissue disorders (9.3%), and psychiatric disorders (5.5%). The most frequently reported single diseases were uveitis in 14.4%, chronic secondary pain syndrome in 4.4%, hypertension in 3.6%, and psoriasis in 3.3%. In addition, inflammatory bowel diseases were reported in 2.5% of cases, other immune-mediated disorders, namely autoimmune thyroiditis in 2.5%, type1 diabetes in 0.7% and celiac disease in 0.3%, depression in 2.3%, anxiety in 0.3%, osteoporosis in 1.6%, and amyloidosis in 0.4%. Among the reported comorbidities, there was one case with a cerebrovascular accident, but none with ischemic heart disease, heart failure or diverticulitis. The rate of comorbid condition accrued in the various JIA categories (table 1 ) differed significantly, with the highest rate in patients with extended oligoarthritis. Conclusions: Young adults with JIA have a high rate of comorbidity overall, with extraarticular JIA manifestations being the most frequently reported comorbid conditions. Comorbidity rates vary among the various JIA categories. Patients with systemic JIA have the highest rate of cardiovascular risk factors and osteoporosis, while patients with extended OA have the highest rate of uveitis. An underreporting or unawareness of comorbidities by rheumatologists is possible, guidance on risk assessment in adults with JIA is needed. Acknowledgements: The authors thank all rheumatologists for contributing patients to the JuMBO registry. BiKeR is funded by unconditional grants from Abbvie, Germany, Novartis, Germany, and Roche, Germany, JuMBO by unconditional grants from Abbvie, Pfizer, and Roche. Disclosure of Interest: K. Minden Speakers bureau: Pfizer, Roche, Pharm-Allergan, N. Betenstehl: None declared, J. Klotsche: None declared, E. Seipelt: None declared, S. Tatsis: None declared, I. Foeldvari: None declared, G. Ganser: None declared, G. Horneff Speakers bureau: Abbvie, Pfizer, Roche, Novartis, MSD